NILAI WAKTU KENDARAAN PRIBADI DI KOTA BANDA ACEH - Noer Fadhly; Roni Agusmaniza (Jurnal Teknik Sipil Unaya, 2015)
The value of travel time becomes an important part of the gains in the assessment of a transport project in terms of economic considerations. In this research, the calculation of the value of travel time for users of private vehicles in Banda Aceh. Purposes of calculating the value of travel time is to vote as a result of a wasted opportunity when used to produce something as a result of traveling purposes. Of the various methods that can be used to determine the value of travel time method selection transport modes (mode choice approach) with a stated preference survey data is either to be used in determining the value of time based on the use of public transport (labi-labi) as the second choice , but taken one more method is the method of income (income approach) as a comparison. As for the results in this study is the comparison of both methods is the method of choice of transport modes (mode choice approach) and method of income (income approach) to obtain the value of travel time for users of private vehicles in the city of Banda Aceh.